2010
DOI: 10.1007/s00253-010-2642-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing itaconic acid production by Aspergillus terreus

Abstract: Aspergillus terreus is successfully used for industrial production of itaconic acid. The acid is formed from cis-aconitate, an intermediate of the tricarboxylic (TCA) cycle, by catalytic action of cis-aconitate decarboxylase. It could be assumed that strong anaplerotic reactions that replenish the pool of the TCA cycle intermediates would enhance the synthesis and excretion rate of itaconic acid. In the phylogenetic close relative Aspergillus niger, upregulated metabolic flux through glycolysis has been descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 27 publications
3
61
1
Order By: Relevance
“…While rational engineering of Aspergillus species has improved itaconic acid titers to 1.4 g/L (Blumhoffa et al 2013;Li et al 2012), the high titers required for industrial production (of more than 80 g/L) have been enabled by efforts utilizing media optimization and large-scale mutagenesis (Kautola et al 1991;Kuenz et al 2012;Yahiro et al 1995). Despite the high itaconic acid titers enabled in A. terreus fermentations, this organism has several drawbacks including being (1) naturally inhibited in media formulated to induce production and (2) negatively impacted by shear stress, preventing cultivation in standard stirred tank bioreactors (Park et al 1994;Tevz et al 2010;Yahiro et al 1995). Metabolic profiling and functional gene characterization in A. terreus demonstrated that itaconic acid production proceeds through the decarboxylation of cis-aconitic acid, a tricarboxylic acid (TCA) cycle intermediate (Bonnarme et al 1995) via the cis-aconitic acid decarboxylase encoding gene (CAD) (Kanamasa et al 2008) (Fig.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…While rational engineering of Aspergillus species has improved itaconic acid titers to 1.4 g/L (Blumhoffa et al 2013;Li et al 2012), the high titers required for industrial production (of more than 80 g/L) have been enabled by efforts utilizing media optimization and large-scale mutagenesis (Kautola et al 1991;Kuenz et al 2012;Yahiro et al 1995). Despite the high itaconic acid titers enabled in A. terreus fermentations, this organism has several drawbacks including being (1) naturally inhibited in media formulated to induce production and (2) negatively impacted by shear stress, preventing cultivation in standard stirred tank bioreactors (Park et al 1994;Tevz et al 2010;Yahiro et al 1995). Metabolic profiling and functional gene characterization in A. terreus demonstrated that itaconic acid production proceeds through the decarboxylation of cis-aconitic acid, a tricarboxylic acid (TCA) cycle intermediate (Bonnarme et al 1995) via the cis-aconitic acid decarboxylase encoding gene (CAD) (Kanamasa et al 2008) (Fig.…”
Section: Introductionmentioning
confidence: 98%
“…Itaconic acid production was first observed in Aspergillus itaconicus in 1932 (Kinoshita 1932) and current industrial fermentation production utilizes a related strain, Aspergillus terreus (Tevz et al 2010). While rational engineering of Aspergillus species has improved itaconic acid titers to 1.4 g/L (Blumhoffa et al 2013;Li et al 2012), the high titers required for industrial production (of more than 80 g/L) have been enabled by efforts utilizing media optimization and large-scale mutagenesis (Kautola et al 1991;Kuenz et al 2012;Yahiro et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In an effect to improve the application potential of itaconic acid, a great deal of research related to itaconic acid biosynthesis (Bonnarme et al 1995;Jaklitsch et al 1991;Li et al 2011) and its regulation mechanism (Huang et al 2014b;Lin et al 2004;Reddy and Singh 2002;Tevz et al 2010) have been carried out to improve the production efficiency of itaconic acid. In addition to enhancing the biosynthesis pathway, disrupting or weakening the degradation pathway by metabolic engineering is also an effective strategy to promote the accumulation of target products.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lin et al (2004) reported that Vitreoscilla hemoglobin expression enhanced itaconic acid production in A. terreus. Tevz et al (2010) also reported that itaconic acid production can be …”
mentioning
confidence: 98%